THE EFFECTIVITY TEST OF SHEEP RUMEN LIQUOR ENZYME ADDED TO PALM KERNEL MEAL ON ITS DECREASE OF CRUDE FIBER AND APPARENT DIGESTIBILITY COEFFICIENT FOR CATFISH Pangasius hypophthalmus DIET - Wahyu Pamungkas; Dedi Jusadi; Nur Bambang Priyo Utomo (Indonesian Aquaculture Journal, 2011)
Two experiments were conducted to evaluate the hydrolysis of fiber content in palm kernel meal (PKM) by sheep rumen liquor enzyme and to know the apparent digestibility coefficient of hydrolyzed PKM for catfish Pangasius hypophthalmus. The first trial examined effectivity of sheep rumen liquor enzyme to decrease crude fiber content of PKM. The added volume of sheep rumen liquor enzyme was 0, 20, 40, 60, 80, and 100 mL/kg PKM and then it was incubated for 0, 12, and 24 hours. A factorial completely randomized experimental design consisted of 2 variables and triplicates were selected. The second trial was conducted to evaluate the apparent digestibility coefficients of hydrolized PKM for catfish. Apparent digestibility coefficients were determined using chromic oxide indicator added to both reference and test diets. The feed ingredients used in the trial were hydrolyzed PKM (PKMe) and unhydrolyzed PKM (PKM). Ten fishes with weighing around 20 g were used in the trial and held in 80 l tanks. Feces were collected from three replicate groups of fish using a fecal collection column attached to fish rearing tank. PKM hydrolyzed with 100 mL/kg and incubated for 24 hour showed the lowest crude fiber content (6.99%) among the treatments (P<0.05). Apparent digestibility coefficient of hydrolyzed PKM was 57.57% compared with unhydrolyzed PKM 15.31%. Based on the evaluation in those parameters it was concluded that sheep rumen liquor enzyme added to PKM was effective to decrease crude fiber content of PKM and improve apparent digestibility coefficient of PKM for catfish.